Dynamics of nitrification in rotating biological contactors - Bravo, Helen E.; Watanabe, Yoshimasa; Lohani, B.N.; Chongrak Polprasert; The Government of the Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1981)
A dynamic model was developed to represent the dynamic responses of nitrification in a fixed-film rotating biological contactor, the key feature of which is the use of the steady state kinetic model to describe substrate-uptake in the biofilm. Results of the experiment showed that during transient operations, a pseudo-steady state concentration distribution is established after a short lapse of time, in the diffusion layer and in the biofilm with respect to the bulk-liquid substrate concentration. There was a transient rise in the ammonia flux at the biofilm surface and the shift to steady state flux level was reached after a few disk rotations. Substrate-uptake rate was observed constant once a certain critical film thickness was exceeded and was not increased by further accumulation of microorganisms on the slime. It was also observed that the nitrifying bacteria exhibited a very small lag in growth rate when exposed to sudden changes in concentration. Furthermore, when the concentration of the products accumulated in excessive amounts it was observed that the out-diffusion of products from the internal pores of the biomass to the outer surface of the film affected the rate of substrate utilization resulting to process instability especially with long term transients. Conclusion based on engineering calculations are presented to illustrate design and operational mode for a more effective control of nitrification in dynamic systems. Simple forcing functions like pulse and step functions were used to verify the dynamic model in the zero-order regime; that is at bulk- ammonia concentration greater than 3 mg/l. Results of the experiment adequately verified the dynamic models developed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Sewage -- Purification -- Rotating disc process; Nitrification